Mother tongue matters: A critical study of indigenous language integration in formal education systems - Adnyana, Ida Bagus Artha; Sitawati, Anak Agung Raka; Ghafar, Zanyar Nathir; Hazaymeh, Omar Mohammad-Ameen Ahmad (Yayasan Mitra Persada Nusantara, 2025)
This study critically examines the integration of indigenous languages in formal education systems, emphasizing the significance of mother tongue instruction in fostering inclusive, culturally relevant, and effective learning environments. The primary aim of this research is to explore the extent to which indigenous languages are incorporated into school curricula, assess the challenges and benefits associated with such integration, and analyse the implications for students’ cognitive development, identity formation, and academic achievement. Drawing on the theoretical frameworks of linguistic human rights and sociocultural learning theory, the study investigates how language policy and pedagogical practices either support or hinder the use of mother tongue instruction. A qualitative research method was employed, utilizing document analysis and semi-structured interviews with educators, policymakers, and community leaders in regions where indigenous language programs are either implemented or lacking. The data collected was thematically analysed to identify recurring patterns, contradictions, and contextual variations in the treatment of indigenous languages within formal education systems. The findings reveal a persistent marginalization of indigenous languages, despite national and international policies advocating for multilingual education. In cases where indigenous languages are integrated, improvements in students’ engagement, comprehension, and cultural pride were noted. However, numerous obstacles persist, including lack of trained teachers, insufficient teaching materials, and limited institutional support. The analysis underscores the need for more inclusive and participatory policy-making that involves local communities and recognizes the pedagogical and cultural value of indigenous languages. In conclusion, the study advocates for a transformative shift in education policy and practice, promoting indigenous languages not only as mediums of instruction but also as essential elements of cultural preservation and empowerment. Effective integration requires collaborative efforts among governments, educators, and indigenous communities to ensure that every child can learn in a language they understand and identify with.